2019
DOI: 10.1111/cid.12727
|View full text |Cite
|
Sign up to set email alerts
|

The chemical surface evaluation of black and white porous titanium granules and different commercial dental implants with energy‐dispersive x‐ray spectroscopy analysis

Abstract: Background The chemical surface structure of the porous titanium grafts has not been found to study in the literature on the similarity of chemical surfaces of different commercial dental implants. Purpose The purpose of this study is to investigate the chemical composition and surface energies of white (WPTG) and black porous titanium granules (PTG) by energy dispersive x‐ray spectrometry (EDX) analysis to compare with different commercial dental implant surface. Materials and Methods The surface chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 35 publications
2
21
3
Order By: Relevance
“…Although it has been proven to be a reliable and a practical method, there is no consensus on the chemical compositions of dental implants. Ti concentration in CP-Ti implants is reported to range approximately from 22.5% [18] to 100% [17], while also finding the existence of some impure contents such as Al, Fe, Si and Na [24]. In this study, EDS compositional maps of the failed implants provide evidence of C and O enrichment in the surrounding bone.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Although it has been proven to be a reliable and a practical method, there is no consensus on the chemical compositions of dental implants. Ti concentration in CP-Ti implants is reported to range approximately from 22.5% [18] to 100% [17], while also finding the existence of some impure contents such as Al, Fe, Si and Na [24]. In this study, EDS compositional maps of the failed implants provide evidence of C and O enrichment in the surrounding bone.…”
Section: Discussionsupporting
confidence: 49%
“…In addition to Ti as a major component of dental implants, O and C are commonly found in the chemical composition of dental implants; all of these are not considered harmful elements [17,18]. However, several studies have reported findings of other elements in the implant surface such as nitrogen (N), F, P, chloride (Cl), and Na together with some inorganic impurities such as Al, zinc (Zn), Si, and Mg, among others [17,19]. These inorganic chemical compositions are suggested to be the products of a corrosion process [20].…”
Section: Discussionmentioning
confidence: 99%
“…The surface contamination due to the adsorption of hydrocarbons present in the atmosphere introduces presence of carbon on the surface; in the second case the titanium signal almost disappeared, the ratios O/Ti and C/Ti increased and the nitrogen rose up to 14%. The presence of this organic molecule confirmed that collagen was in the titanium surface [ 62 ].…”
Section: Studies On Surface Modifications Of Dental Implants Using Hamentioning
confidence: 90%
“…Energy-dispersive X-ray spectroscopy (EDX) is useful for studying the elemental composition of mineralized tissues or mineral deposits (apatite). In addition, it can detect elements that may have migrated from an implant material to the bone tissue [ 10 ].…”
Section: Introductionmentioning
confidence: 99%